Biochars from agro-industrial residues of the Amazon: an ecological alternative to enhance the use of phosphorus in agriculture - Canteral, Kleve Freddy Ferreira [UNESP]; Dias, Yan Nunes; Fernandes, Antonio Rodrigues (Springer Nature, 2023)
The growth of the world population requires greater agricultural production, which consequently increases the demand for phosphorus-based (P-based) compounds and the generation of agro-industrial residues. Biochar is an effective alternative for the recovery and reuse of P-based species, as well to mitigate the generation of environmental liabilities and provide adequate disposal for agro-industrial residues. This study investigates the phosphate adsorption capacity of biochars produced with residues of açaí seeds (BA), Brazil nut shell (BN) and palm kernel cake (BK) and the relationship with their chemical constituents. Biochars were produced at 700 ºC to evaluate the physicochemical properties, elemental composition, contact time and influence of pH on phosphate adsorption. The solid/liquid contact time varied from 1 to 24 h and the adsorption of phosphorus species on biochar was strongly pH dependent (p < 0.05) between the biochars (BN > BA > BK). The Langmuir isotherm model best described the adsorption process (R2 ≥ 0.90) and showed high efficiency in phosphate removal in aqueous solution (BA: 92.34; BN: 123.55 and BK: 79.46 mg g–1). The heterogeneity of mineral constituents was emphasized by principal component analysis and indicated that phosphate adsorption on biochars is highly and directly associated with carbon (C) content, cation exchange capacity and pH and inversely related to nitrogen (N) content, yield, point of zero charge, (O + N)/C and ash content. Therefore, these biochars constitute promising materials for phosphate adsorption and present potential to be applied to soil as a source of P in the form of biofertilizer. Graphical abstract: [Figure not available: see fulltext.]
Keywords: Biomass residue; Isotherm; Phosphorus adsorption capacity; Phosphorus recovery